Short video TikTok in EFL: How does it impact students' vocabulary mastery - Maria, Leni; Sujarwati, Iis (Indonesian Journal of Educational Development (IJED), 2025)
While TikTok videos have shown promising effects on vocabulary learning among junior and senior high school students, further research is warranted to assess their impact on vocabulary mastery in twelfth-grade students specifically. This study seeks to evaluate the effectiveness of TikTok videos in enhancing vocabulary mastery among twelfth-grade students in senior high school. Employing a quasi-experimental design, the research involved 70 students divided equally into an experimental group and a control group. The data were collected in both groups through pre-tests and post-tests using multiple-choice items to measure students’ vocabulary mastery. The results from the statistical analysis of the paired-sample t-test indicated a significant improvement in vocabulary mastery for students using TikTok videos. This made strong evidence that TikTok videos were significantly effective in enhancing vocabulary acquisition among the twelfth-grade students. Although the study involved only a specific group of words, it offers valuable insights for educators seeking innovative strategies to improve students’ vocabulary acquisition through engaging digital media.